Design and simulation of a graphene-integrated SPR biosensor for malaria detection - Tene, Talia; Arias Arias, Fabian; Paredes-Páliz, Karina I.; González García, Juan Carlos; Bonilla García, Nataly; Vacacela Gomez, Cristian (Frontiers in Bioengineering and Biotechnology, 2025)
This work presents the theoretical design and optimization of a surface plasmon resonance (SPR) biosensor incorporating graphene, silicon nitride, and a thiol-tethered ssDNA layer for malaria detection and stage differentiation. Two configurations (Sys3 and Sys4) were simulated using the transfer matrix method to determine optimal material thicknesses. The final designs were evaluated against three malaria stages—ring, trophozoite, and schizont—based on their refractive index variations. Sys3 achieved sensitivities of 353.14, 291.14, and 263.26°/RIU, while Sys4 reached 315.71, 294.81, and 268.65°/RIU, respectively. These values exceed those reported in comparable SPR platforms. Sys3 showed enhanced optical performance with a higher quality factor and lower detection limit, whereas Sys4 offered improved biomolecular recognition. Although limited to simulation, the proposed configurations demonstrate potential for label-free, stage-specific malaria diagnostics, supporting future development toward point-of-care applications.